Photovoltaic, wireless wide‐field epiretinal prosthesis to treat retinitis pigmentosa - Schulz, André; Knoll, Thorsten; Jaeger, Tino; Le Harzic, Ronan; Stracke, Frank; Wien, Sascha L.; Olsommer, Yves; Meiser, Ina; Wagner, Sylvia; Rammensee, Michael; Kurz, Oliver; Klesy, Stephan; et al. (Acta ophthalmologica (Oxford, England), 2025)
Purpose To develop and evaluate a photovoltaic, wireless wide‐field epiretinal prosthesis for the treatment of retinitis pigmentosa. Methods A mosaic array of thinned silicon‐based photodiodes with integrated thin‐film stimulation electrodes was fabricated with a flexible polyimide substrate film to form a film‐based miniaturized electronic system with wireless optical power and signal transmission and integrated electrostimulation. Manufactured implants were characterized with respect to their optoelectronic performance and biocompatibility following DIN EN ISO 10993. Results A 14 mm diameter prosthesis containing 1276 pixels with a maximum sensitivity at a near infrared wavelength of 905 nm and maximized stimulation current density 30–50 μm below the electrodes was developed for direct activation of retinal ganglion cells during epiretinal stimulation. Fabricated prostheses demonstrated mucosal tolerance and the preservation of both metabolic activity, proliferation and membrane integrity of human fibroblasts as well as the retinal functions of bovine retinas. Illumination of the prosthesis, which was placed epiretinally on an isolated perfused bovine retina, with infrared light resulted in electrophysiological recordings reminiscent of an a‐wave (hyperpolarization) and b‐wave (depolarization). Conclusions A photovoltaic, wireless wide‐field epiretinal prosthesis for the treatment of retinitis pigmentosa using near infrared light for signal transmission was designed, manufactured and its biocompatibility and functionality demonstrated in vitro and ex vivo.